2019
DOI: 10.1371/journal.pone.0212273
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of leukocyte telomere length in pregnant women living with HIV, and HIV-negative pregnant women: A longitudinal observational study

Abstract: Background HIV-mediated inflammation and immune activation can accelerate telomere attrition. In addition, antiretrovirals can inhibit telomerase, possibly shortening telomeres. We examined the longitudinal dynamics of leukocyte telomere length (LTL) during pregnancy in a unique cohort of women living with HIV (WLWH) treated with combination antiretroviral therapy (cART), and HIV-negative control women. Methods Blood was collected at three visits during pregnancy, at 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…We found evidence of leukocyte telomere length as a marker of biological aging in Rwandan women and also of possible associations between maternal micronutrient status and leukocyte telomere length in pregnant women in Rwanda. Other leukocyte telomere length studies with pregnant women have been conducted primarily in the European and North American context, which presents a different environmental milieu in terms of overall burden of infectious disease and maternal nutritional health [38,39]. In contrast with these other studies, the endemicity of infectious diseases in Kigali, Rwanda, including clinical and subclinical infections such as a higher prevalence of sexually transmitted infections and endemicity of malaria, provides a different context to assess the association between maternal leukocyte telomere length and birth outcomes [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found evidence of leukocyte telomere length as a marker of biological aging in Rwandan women and also of possible associations between maternal micronutrient status and leukocyte telomere length in pregnant women in Rwanda. Other leukocyte telomere length studies with pregnant women have been conducted primarily in the European and North American context, which presents a different environmental milieu in terms of overall burden of infectious disease and maternal nutritional health [38,39]. In contrast with these other studies, the endemicity of infectious diseases in Kigali, Rwanda, including clinical and subclinical infections such as a higher prevalence of sexually transmitted infections and endemicity of malaria, provides a different context to assess the association between maternal leukocyte telomere length and birth outcomes [40].…”
Section: Discussionmentioning
confidence: 99%
“…We found no association between biomarkers for inflammation and infection including sexually transmitted infections and leukocyte telomere length, although in bivariate analyses, any presence of sexually transmitted infection and infection with chlamydia trachomatis approached statistical significance for shorter leukocyte telomere length. Previous studies of infectious disease, specifically HIV in South Africa, have found shorter leukocyte telomere length with infection [59] although other studies with HIV infected individuals did not find any association, primary in the context of antiretroviral therapy immune reconstitution [38,60]. Additional studies evaluating multiple pathogens have found that the association between shorter leukocyte telomere and infection may be pathogen specific [61].…”
Section: Infections and Inflammationmentioning
confidence: 94%
“…We observed that shorter LTLs in HIV + individuals were strongly associated with advancing age, cART without INSTI, failure to achieve viral control after initiation of cART, and substance use. In previous reports, cART and substance abuse have sometimes been associated with LTL shortening in HIV + individuals [25, 26]. Antiretroviral drug-induced toxicity is an important complication of cART, particularly for regimens containing protease inhibitors (PIs).…”
Section: Discussionmentioning
confidence: 99%
“…Telomere attrition typically occurs gradually in adults, although the inter-individual variability is high [31]. Nevertheless, studies have detected changes in LTL in response to various interventions (e.g., calorie-restricted diet resulting in weight loss, exercise, and meditation) and pregnancy in less than 12 weeks [32][33][34][35]. There remains an extensive gap in the literature regarding short-term changes in telomere length.…”
Section: Introductionmentioning
confidence: 99%